1994
DOI: 10.1017/s0965539500000954
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiovascular reflex responses to hypoxaemia

Abstract: The fetus mounts a coordinated cardiovascular response to an insult of acute hypoxaemia which involves neural and endocrine components. During acute hypoxaemia in late pregnancy there is a transient bradycardia, a gradual increase in arterial blood pressure and an increase in heart rate variability. In addition, there is a redistribution of the combined ventricular output favouring the cerebral, myocardial and adrenal circulations by shunting blood away from the peripheral circulations. A component of the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
127
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 130 publications
8
127
0
1
Order By: Relevance
“…A total of 120 chick embryos were used in this study. On days 11,15, and 19 of incubation, 10 chick embryos were randomly assigned to a control group and 10 to an experimental group. Cardiac output distribution was determined by injection of 15-m fluorescent microspheres (Fluospheres, Molecular Probes, Eugene, OR) suspended in saline and 0.05% Tween 80 (1 ϫ 10 6 spheres/ml), as previously described (22,23).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 120 chick embryos were used in this study. On days 11,15, and 19 of incubation, 10 chick embryos were randomly assigned to a control group and 10 to an experimental group. Cardiac output distribution was determined by injection of 15-m fluorescent microspheres (Fluospheres, Molecular Probes, Eugene, OR) suspended in saline and 0.05% Tween 80 (1 ϫ 10 6 spheres/ml), as previously described (22,23).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The mechanisms mediating the fetal cardiovascular response to hypoxemia are triggered by carotid chemoreceptor stimulation, which elicits bradycardia, hypertension, and a redistribution of the cardiac output in favor of the adrenal gland, the heart, and the brain (10). Neural sympathetic stimulation and endocrine vasopressor substances, such as catecholamines, contribute to peripheral vasoconstriction, prioritizing the fetal cardiac output away from the periphery to the more vital organs (11,12,14). Previous studies from our laboratory have demonstrated the importance of catecholamine release in the cardiovascular response to an episode of acute hypoxemia in the chick embryo.…”
mentioning
confidence: 99%
“…The Physiology of the "Fetal Brain Sparing" Response The physiology underlying the fetal brainsparing effect in hypoxic pregnancy is well established and involves neural reflexes triggered by the carotid body and endocrine and local factors in the fetus, which ultimately constrict peripheral circulations and dilate essential vascular beds (6). Consequently, the fetal cardiac output is redistributed, shunting blood flow away from peripheral and toward essential vascular beds, such as those perfusing the brain.…”
mentioning
confidence: 99%
“…Measurement of the level of Pao2 (but not Sao2, Cao2 or 0 2 delivery) is important as it is a potent stimulus to the arterial chemoreceptors, especially the carotid bodies, which initiate the rapid cardiovascular reflexes which occur in the fetus during an episode of acute hypoxia [6]. However, whilst fetal blood samples can be taken by cordocentesis [7], the method is not feasible intra-partum.…”
Section: Measurement Of Oxygenationmentioning
confidence: 99%
“…The problem is exacerbated if the oximetry probe is applied to the scalp or cheek, as is usual intrapartum, for the signal will be derived at least partially from cutaneous blood. This flow is particularly sensitive to neural and endocrine-mediated vasoconstriction which occurs in hypoxaemia [6], and indeed the linear rela tion between skin blood flow and plasma cate cholamines has been used as a measure of fetal stress responses to hypoxaemia [8] (see Fig. 5).…”
Section: A Hanson Jg Nijhuis / European Journal O F Gynecologymentioning
confidence: 99%